Study Effect of Periostin Level in Obese Iraqi Females Patients with Type 2 Diabetes Mellitus - Layla Othman Farhan; Ahmed Abduljabar Al-Sabbagh; Baydaa Ahmed Abed; Ahlam M. Farhan; Noor Ulhuda G. Mohammed (Medical Journal of Babylon)
Background: Obesity has been connected to a higher risk of acquiring a number of diseases, including cancer, type 2 diabetes mellitus (T2DM), hypertension, and cardiovascular disease. Periostin is a crucial regulator of the growth and maintenance of bones, teeth, and the heart. Objectives: The aim of the study was to estimate the level of (periostin, glycated hemoglobin [HbA1c], fasting serum [FBG], total cholesterol [TC], high-density lipoprotein [HDL], low-density lipoprotein [LDL], and triglycerides [TG]) in diabetic Iraqi women obese and nonobese. Materials and Methods: Ninety participants were chosen for this study: 30 nonobese female patients with T2DM (nonobese-T2DM), 30 obese female patients with T2DM (obese-T2DM), and 30 healthy participants. Age ranges between 35 and 65 years. Results: The result of the present study found a highly significant increase in the (body mass index [BMI], FBG, HbA1c, TC, TG, LDL, and periostin) in obese-T2DM and nonobese-T2DM when compared with the healthy control group, whereas HDL was lower in obese-T2DM and nonobese-T2DM when compared with the healthy control group. Conclusion: The current investigation discovered, in summary, that plasma periostin may function as a novel marker for insulin resistance, obesity, and inflammatory responses, which might be used to diagnose T2DM and obesity.